Acute Intestinal Obstruction in Meckel’s Diverticulum - I. H. Shidakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present of a clinical case of a rare complication of Meckel’s diverticulum (MD).General findings. Diseases caused by the presence of MD present one of the most common causes of an “acute abdomen” in children: up to 60% of cases of their manifestation occur in children under 10 years of age. The most common MD manifestations involve complications, such as intestinal obstruction, bleeding, diverticulitis and Litre hernia. A 9-year-old girl with abdominal pain and vomiting having appeared several hours before hospitalization was admitted to a paediatric surgical department. A few hours later, the child was operated. In the course of surgery, a strangulated intestinal obstruction was found on the mesodiverticular ligament connecting Meckel’s diverticulum with the root of the small intestine mesentery. As a result, a diverticulum resection and bowel obstruction were performed. The child was discharged with recovery.Conclusions. An inversion of the intestine around the mesodiverticular ligament appears to be one of the most rare complications of MD. In this case, the delayed diagnosis results in the development of formidable complications in the form of necrosis and intestinal perforation, which makes Meckel’s diverticulum one of the most dangerous conditions in children.